Nodal Upstaging Evaluation After Robotic-Assisted Lobectomy for Early-Stage Non-small Cell Lung Cancer Compared to Video-Assisted Thoracic Surgery and Thoracotomy: A Retrospective Single Center Analysis - Gallina, Filippo Tommaso; Melis, Enrico; Forcella, Daniele; Mercadante, Edoardo; Marinelli, Daniele; Ceddia, Serena; Cappuzzo, Federico; Vari, Sabrina; Cecere, Fabiana Letizia; Caterino, Mauro; Vidiri, Antonello; Visca, Paolo; et al. (Frontiers in Surgery, 2021)
Introduction The standard surgical procedures for patients with early stage NSCLC is lobectomy associated radical lymphadenectomy performed by using the thoracotomy approach. In the last few years, minimally invasive techniques have increasingly strengthened their role in lung cancer treatment, especially in the early stage of the disease. Although the lobectomy technique has been accepted, controversy still surrounds lymph node dissection. In our study, we analyzed the rate of upstaging early non-small cell lung cancer patients who underwent radical surgical treatment using the robotic and the VATS techniques compared to the standard thoracotomy approach. Materials and Methods We retrospectively reviewed patients who underwent a lobectomy and radical lymphadenectomy at our Institute between 2010 and 2019. We selected 505 patients that met the inclusion criteria of the study: 237 patients underwent robotic surgery, 158 patients had thoracotomy and 110 patients who were treated with VATS. We analyzed the demographic features between the groups as well as the nodal upstaging rate after pathological examination, the number of dissected lymph nodes and the ratio between dissected lymph nodes and metastatic lymph nodes between the three groups. Results The patients of the three groups were homogenous with respect to age, sex and histology. The postoperative major morbidity rate was significantly higher in the thoracotomy group and hospital stay was significantly longer. The percentage of the mediastinal nodal upstaging rate and the number of dissected lymph nodes was significantly higher in the robotic group compared to the VATS group. The ratio between dissected lymph nodes and metastatic lymph nodes resulted significantly lower compared to the VATS group and the thoracotomy group. Discussion The prognostic impact of the R(un) status is still highly debate. The surgical approach that allows better results in terms of resection has still not been defined. Our results show that robotic surgery is a safe and feasible approach especially regarding the accuracy of mediastinal lymphadenectomy. These findings can lead to defining a more precise pathological stage of the disease and, if necessary, to more accurate postoperative treatment.